CASE COMMENT ON NATIONAL LEGAL SERVICES AUTHORITY V. UNION OF INDIA & OTHERS (AIR 2014 SC 1863): A RAY OF HOPE FOR THE LGBT COMMUNITY - M.K. Sahu (BRICS Law Journal, 2016)
The lives of human beings are full of complexities, but LGBT face much more trauma compared to other people. What is necessary is to understand the sentiments of the LGBT community and also to grant them common human rights. But the world lowers its eyes and refuses a discussion over the granting of basic human rights to the LGBT community. And it is so sad to see that such discrimination exists even in the 21st century. Indian law, on the whole, only recognizes the paradigm of the binary genders of male and female, based on a person’s sex assigned at birth, which permits a gender system, including the laws relating to marriage, adoption, inheritance, succession and taxation, and welfare legislation. The most pertinent question with respect to the LGBT community is whether LGBT are to be discriminated against by other human beings. Merely being different does not give others the authority to ostracize one from society. In fact, in July 2009 the Delhi High Court ruled that consensual same-sex relations between adults in private could not be criminalized. Then in a recent judgment, the Supreme Court of India expressed its concerns over the mental trauma, emotional agony and pain of the members of the transgender community: all forms of mental suffering of the LGBT community, as well as ignorance and isolation of the community, were brought to an end by the Court’s decision in National Legal Services Authority v. Union of India & Others.